1992
DOI: 10.1007/bf02245111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated MK-801 on ambulation in mice and in sensitization following methamphetamine

Abstract: The noncompetitive NMDA receptor antagonist MK-801, (+)-5-methyl-10,11-dihydro-5H-dibenzo-[a,d]-cyclohepten-5,10-imine , increased ambulatory activity in the mouse at doses over 0.1 mg/kg (IP). The effect was enhanced when 0.3 mg/kg MK-801 was repeatedly administered at intervals of 3-4 days. In contrast, a reduction of the effect was induced with repeated doses of 0.1 and 1 mg/kg. The mice that had repeatedly experienced 1 mg/kg MK-801 exhibited a decrease in the sensitivity to methamphetamine (2 mg/kg SC). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 17 publications
4
24
1
Order By: Relevance
“…Thirdly, it seems unlikely that D-CPPene, a competitive NMDA receptor antagonist, acts on nicotinic receptors in the way reported for channelblockers such as mecamylamine or dizocilpine. Finally, as cited above, dizocilpine attenuates adaptive changes to other psychostimulants, opioids and alcohol, substances that do not interact potently with nicotinic receptors (Karler et al, 1989;Wolf & Khanza, 1991;Kuribara et al, 1992). It seems reasonable to conclude that an antagonist effect at NMDA receptors is more likely than nicotinic blockade to be the mechanism by which dizocilpine and D-CPPene influenced responses to nicotine.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Thirdly, it seems unlikely that D-CPPene, a competitive NMDA receptor antagonist, acts on nicotinic receptors in the way reported for channelblockers such as mecamylamine or dizocilpine. Finally, as cited above, dizocilpine attenuates adaptive changes to other psychostimulants, opioids and alcohol, substances that do not interact potently with nicotinic receptors (Karler et al, 1989;Wolf & Khanza, 1991;Kuribara et al, 1992). It seems reasonable to conclude that an antagonist effect at NMDA receptors is more likely than nicotinic blockade to be the mechanism by which dizocilpine and D-CPPene influenced responses to nicotine.…”
Section: Discussioncontrasting
confidence: 40%
“…There have been recent reports that pretreatment with dizocilpine (MK-801), a non-competitive N-methyl-D-aspartate (NMDA) receptor antagonist, weakens or prevents the development of adaptations to diverse drugs including CNS stimulants such as amphetamine, methamphetamine and cocaine (Karler et al, 1989;Kuribara et al, 1992;Wolf & Khansa, 1991;Schenk et al, 1993), opioids such as morphine (Trujillo & Akil, 1990;Ben-Eliyahu et al, 1992) and alcohol (Morriset et al, 1990 receptors may play a role in the adaptive responses to nicotine since, when rats are exposed chronically to dizocilpine, as well as to nicotine, the usual sensitization reaction to the locomotor stimulant effect of nicotine fails to develop (Shoaib & Stolerman, 1992b). These data have been interpreted as evidence that activation of NMDA receptors may be a necessary step in the development of sensitization to nicotine.…”
Section: Introductionsupporting
confidence: 41%
“…It is not clear whether such a mechanism con tributes to the production of the ketamine-induced reverse tolerance as demonstrated in our study. Phencycli dine (13) and MK-801 (14), which are similar to ketamine in behavioral and NMDA antagonistic properties (4), are reported to produce the reverse tolerance to their ambula tion-increasing effect after the repeated administration, but not a cross-sensitization to amphetamines. Ketamine sensitized mice also do not display the cross-sensitization to methamphetamine (Y. Uchihashi, unpublished data).…”
mentioning
confidence: 42%
“…Ketamine sensitized mice also do not display the cross-sensitization to methamphetamine (Y. Uchihashi, unpublished data). These results suggest that the reverse tolerance to keta mine is produced through a different dopaminergic mechanism from that of amphetamines, probably via an agonistic action on sigma receptors and/or an antagonis tic action on NMDA receptors (13,14). Livingston and Waterman (9) demonstrated that the tolerance to the hypnotic action of ketamine is associated with an increased hepatic metabolism in rats.…”
mentioning
confidence: 44%
“…In our previous study (13), the coadministration of MK-801 with methamphetamine potentiated the ambulation-increasing effect. However, a comparatively higher dose of MK-801 (1 mg/kg) rather inhibited the development of sensitization to methamphetamine.…”
mentioning
confidence: 45%